E-Institute Adminstrative System - TS, Sampritha; V, Bhavya; S, Poornima; AM, Durga Shree; H, Aditya Pai (International Journal of Computer Sciences and Engineering, 2025)
Although a lot of complaint registering website are already available for the students but still a more sophisticated website is required to provide secure two way communications. Thus this portal is proposed for registering valid student complaint about the inconvenience faced in the institution by creating a website and also provides the status of the complaint to the student and the parent. Here the web application is designed using php which uses xampp and wamp server.